The Manufacture of reconstituted snack flakes from sweet potato - Badion, Paul S. (College of Engineering, 1997)
Product: Camote snack flakes -- Plant location: Carmona, Cavite -- Annual volume of production: 203 metric tons -- Annual gross sales: Php 30.6 million -- Annual income: Php 2.5 million -- Total investment cost: Php 23.2 million -- Product unit cost: Php 3.50 (per pack of 30g net weight) -- Product selling price: Php 4.50 (per pack of 30g net weight) -- Return on investment: 10.8% -- Payback period: 3.7 years